Does pre-existing cognitive impairment impact on amount of stroke rehabilitation received? An observational cohort study. (September 2019) - Longley, Verity; Peters, Sarah; Swarbrick, Caroline; Rhodes, Sarah; Bowen, Audrey
Objective: To examine whether stroke survivors in inpatient rehabilitation with pre-existing cognitive impairment receive less therapy than those without. Design: Prospective observational cohort. Setting: Four UK inpatient stroke rehabilitation units. Participants: A total of 139 stroke patients receiving rehabilitation, able to give informed consent/had an individual available to act as personal consultee. In total, 33 participants were categorized with pre-existing cognitive impairment based on routine documentation by clinicians and 106 without. Measures: Number of inpatient therapy sessions received during the first eight weeks post-stroke, referral to early supported discharge, and length of stay. Results: On average, participants with pre-existing cognitive impairment received 40 total physiotherapy and occupational therapy sessions compared to 56 for those without (mean difference = 16.0, 95% confidence interval (CI) = 2.9, 29.2), which was not fully explained by adjusting for potential confounders (age, sex, National Institutes of Health Stroke Scale (NIHSS), and pre-stroke modified Rankin Scale (mRS)). While those with pre-existing cognitive impairment received nine fewer single-discipline physiotherapy sessions (95% CI = 3.7, 14.8), they received similar amounts of single-discipline occupational therapy, psychology, and speech and language therapy; two more non-patient-facing occupational therapy sessions (95% CI = –4.3, –0.6); and nine fewer patient-facing occupational therapy sessions (95% CI = 3.5, 14.9). There was no evidence to suggest they were discharged earlier, but of the 85 participants discharged within eight weeks, 8 (42%) with pre-existing cognitive impairment were referred to early supported discharge compared to 47 (75%) without. Conclusion: People in stroke rehabilitation with pre-existing cognitive impairments receive less therapy than those without, but it remains unknown whether this affects outcomes.